Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Photosynthetic response of Quercus ilex L. plants grown on compost and exposed to increasing photon flux densities and elevated CO 2 - Arena, C.; Vitale, L.; Santo, A. Virzo De (Photosynthetica, 2005)
Quercus ilex plants grown on two different substrates, sand soil (C) and compost (CG), were exposed to photosynthetic photon flux densities (PPFD) at 390 and 800 µmol(CO2) mol -1 (C390 and C800). At C800 both C and CG plants showed a significant increase of net photosynthetic rate (PN) and electron transport rate (ETR) in response to PPFD increase as compared to C390. In addition, at C800 lower non-photochemical quenching (NPQ) values were observed. The differences between C390 and C800 were related to PPFD. The higher PN and ETR and the lower dissipative processes found in CG plants at both CO2 concentrations as compared to C plants suggest that substrate influences significantly photosynthetic response of Q. ilex plants. Moreover, short-term exposures at elevated CO2 decreased nitrate photo-assimilation in leaves independently from substrate of growth.
Keywords: chlorophyll fluorescence induction; electron transport rate; irradiance; nitrate; non-photochemical quenching; oak

Photosynthetic response of Quercus ilex L. plants grown on compost and exposed to increasing photon flux densities and elevated CO 2 - Arena, C; Vitale, L; Santo, A Virzo De (Photosynthetica, 2005)
Quercus ilex plants grown on two different substrates, sand soil (C) and compost (CG), were exposed to photosynthetic photon flux densities (PPFD) at 390 and 800 µmol(CO2) mol -1 (C390 and C800). At C800 both C and CG plants showed a significant increase of net photosynthetic rate (PN) and electron transport rate (ETR) in response to PPFD increase as compared to C390. In addition, at C800 lower non-photochemical quenching (NPQ) values were observed. The differences between C390 and C800 were related to PPFD. The higher PN and ETR and the lower dissipative processes found in CG plants at both CO2 concentrations as compared to C plants suggest that substrate influences significantly photosynthetic response of Q. ilex plants. Moreover, short-term exposures at elevated CO2 decreased nitrate photo-assimilation in leaves independently from substrate of growth.
Keywords: chlorophyll fluorescence induction; electron transport rate; irradiance; nitrate; non-photochemical quenching; oak

Detection of vegetation stress and nutrient deficiencies by leaf laser-induced fluorescence imaging - Heisel, F; Sowinska, M; Eckert, C; Miehe, J A (INTERNATIONAL SYMPOSIUM ON URBAN TREE HEALTH, 1999)
A high spatial resolution fluorescence imaging set-up developed in our laboratory has been used to study the effects of several stress factors on the fluorescence characteristics of various plants. Measurement campaigns, of agricultural interest, have made obvious for example: a strong and specific heterogeneity of the chlorophyll emission distribution at the surface of vine leaves (Vitis Vinefera `Riesling') suffering from different mineral stress for increasing nitrogen fertilisation of wheat (Triticum aestivum L., `Soissons'), a readily decrease of the blue/red and blue/far-red emissions ratios, which were found the most sensitive indicators of a nitrogen deficiency in the case of apple-trees (Malus x domestica Borkh.cv.'Jonagold 2361') an effect of nitrogen supply on the chlorophyll emission intensities, in an opposite way for 355 nm excitation for the rosette leaves than for the leaves from the youngest branches for oak (Quercus ilex) and beech (Fagus sylvatica), an important enhancement of the chlorophyll emission when the solar irradiance during growth is strongly reduced.
Keywords: irradiance; mineral or nitrogen deficiency; vine

RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES - Gratani, L (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.
Keywords: irradiance; leaf area; microclimate; Phillyrea latifolia L.; Pistacia lentiscus L.; Quercus ilex L.

RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES - GRATANI, L. (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.
The following values have no corresponding Zotero field: pub-location: NA KARLOVCE 1A, PRAGUE 6, CZECH REPUBLIC CS-160 00 publisher: INST EXPERIMENTAL BOTANY, ACAD SCI CZECH REPUBLIC
Keywords: irradiance; leaf area; microclimate; Phillyrea latifolia L.; Pistacia lentiscus L.; Quercus ilex L.